An evidence-based comparison of construction project delivery - Plugge, Philip Warren, author; De Miranda, Michael A., advisor; Griffin, G. Scott, advisor; Albright, Leonard, committee member; Criswell, Marvin E., committee member (Colorado State University. Libraries, 2007)
Medical professionals use evidence-based decision theory to identify uncertainty and knowledge about a problem through research and practical knowledge. Doctors use a gestalt process to synthesize the information available, weighting individual pieces of information related to patient condition, resources, budget, experiential knowledge, and econometrics, to analyze potential risks to a patient. As with a patient, construction projects are all unique and take on their own characteristics throughout the life of the project. This research used the analysis-of-variance (ANOVA) method to analyze the risks associated with economics, environment, project, and technology on the project delivery methods of design-bid-build and design-build from the perspective of professionals in the construction industry. Data collected from this research was used to develop an evidence-based risk model related to the constructs of economics, environment, project, and technological risk and compare them between the two project delivery method variables of design-bid-build and design-build. Findings included significant differences across the constructs of project and technology. Additional findings on cost and time exposed differences associated with expectations of change and the understanding of costs within the design-build delivery method. For the design-bid-build project delivery method, the research confirmed the concern about cost growth through change orders. With design-build, the research supported the concept of improved quality and a better understanding of cost during the design process. Significant findings were categorized around the constructs of project and technology. Conclusions from this research provide construction managers associated with the ownership, design, and construction of projects with information about areas and magnitudes of potential risk concerning the two project delivery methods investigated.
Keywords: civil engineering; systems design; design build construction; studies; bids; operating systems; software; decision making; design; systems science; building codes